Our polar flight - Amundsen, Roald; Amundsen, Rual; Amundsen, Roald Engelbregt Gravning; Ellsworth, Lincoln (Project Gutenberg, 2023)
The expedition, by R. Amundsen -- The Amundsen-Ellsworth polar flight, by L. Ellsworth -- The navigator's task, by H. Riiser-Larsen -- Report about N 24 from the start until we joined N 25 and its crew on the 26th May, by L. Dietrichson -- Whilst we wait: leaves from the diary of F. Ramm from May 21st to June 18th -- The weather, by J. Bjerkens.